Understanding Sleep and Dreaming - Moorcroft, William H. (Springer US : Imprint: Springer, 2005)
Although sleep has been the subject of serious study for several decades, there has not been available an integrated, introductory text for more than ten years. Understanding Sleep and Dreaming fills this need with complete coverage of all aspects of sleep, dreaming, and sleep disorders, and is comprehensible as well as comprehensive. In accessible language, this text reviews the basic physiological mechanisms of sleep and the intertwined psychological ramifications. Most important, it is up-to-date, containing the latest information on the influence of orexin/hypocretin, nocturnal eating syndrome, the local cell theory of sleep, the effects of sleep deprivation, and the advantages of delaying school start times for teenagers. Distilling twenty five years of combined clinical, research, and teaching experience, Dr. Moorcroft has created an excellent text for undergraduates, graduate students, and professionals as well as for the general reader who wants a better understanding of the sleep process and its disorders.